Functional and neurochemical development in the normal and degenerating mouse retina. Issue 6 (20th February 2013) - Gibson, Riki; Fletcher, Erica L.; Vingrys, Algis J.; Zhu, Yuan; Vessey, Kirstan A.; Kalloniatis, Michael
Abstract The rd1 mouse is a well‐established animal model for human retinitis pigmentosa (RP). We used electroretinography (ERG) to evaluate retinal function and postembedding immunocytochemistry to determine the changes in cellular amino acid expression in the normal (C57Bl6) and degenerating mouse retina (rd1), as a function of age during development and the onset of degeneration. In the normal mouse retina, photoreceptoral and post‐photoreceptoral ERG responses improved simultaneously from eye‐opening until adult levels were achieved at approximately postnatal day (P) 30. Maturation of amino acid neurochemistry preceded the development of retinal function in the normal retina. Amino acid levels increased immediately from birth and reached stable levels by eye‐opening. In contrast, in the rd1 mouse, both rod and cone pathway function rapidly reduced from eye‐opening and by P21 became undetectable. Interestingly, at P18 cone responses were still comparable between the normal and degenerating retina. Before eye opening, the pattern of amino acid immunoreactivity in the rd1 retina was similar to the normal retina. Alterations in neurochemistry were observed after the onset of rod photoreceptor cell death. The most obvious change was the reduction in neurotransmitter immunoreactivity within the synaptic layers and some cell classes of the rd1 retina. Reduction of glutamine and glutamate was observed in Müller cells before established gliosis markers. Overall, these results suggest the rapid maturation of neurochemistry by eye opening followed by functional maturation by P30 in the normal retina. The dystrophic retina displays similar neurochemistry to control retina before eye opening but a subsequent decline. J. Comp. Neurol. 521:1251–1267, 2013. © 2012 Wiley Periodicals, Inc.